PENINGKATAN PROMOSI PRODUK UMKM MELALUI PENGURUSAN IZIN USAHA: PENINGKATAN PROMOSI PRODUK UMKM MELALUI PENGURUSAN IZIN USAHA - Viki, Viki Masruroh; Putra Wibowo, Ari; Jayanti, Dwi; Anna, Hikmah; Eras Sadela, Adion (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
One of the superior products originating from the village of Bongsopotro is that many people make and sell pentols both around the village of Bongsopotro and outside the village of Bongsopotro. The pentol business actors in Bongsopotro Village merged into the pentol seller association, namely the Sido Mulyo Joint Business Group (KUBE) which was legalized by an establishment decree signed by the head of the Bongsopotro Village. However, some of these businesses have not yet obtained a business license, one of which is the pentol business. Licensing is needed for business actors to support the business they run. From this background, the objectives of the KKN work program are to empower MSMEs and increase the promotion of MSME products through obtaining business permits.